Postoperative care after tonsillectomy: what's the evidence?. Issue 6 (December 2017) - Carpenter, Patrick; Hall, Daniel; Meier, Jeremy D.
Abstract : Purpose of review: The purpose of this review is to evaluate the current literature regarding postoperative management after tonsillectomy in children. Recent findings: Controversy remains regarding the ideal medication regimen to manage pain after tonsillectomy. Acetaminophen and ibuprofen are routinely used, although concerns of more severe postoperative hemorrhage with ibuprofen remain. Narcotics are prescribed commonly, but with extreme caution in children with severe obstructive sleep apnea. Although not always utilized by the authors, additional adjunctive medications such as perioperative dexamethasone, ketamine, and local infiltration of lidocaine into tonsillar pillars may decrease postoperative pain. Systematic reviews have shown that dexamethasone does not increase risk of posttonsillectomy bleeding. Summary: Adenotonsillectomy is one of the most common procedures performed on children and may have significant morbidity from postoperative pain and bleeding. Managing pain remains challenging and the optimal treatment regimen has not been definitively identified. Many medications and alternative therapies have been studied and suggest possible benefit.